Vitamin D fortification of foods in India: present and past scenario. Issue 193 (October 2019) - Jan, Yasmeena; Malik, Muneeb; Yaseen, Mifftha; Ahmad, Sayeed; Imran, Mohammad; Rasool, Suhail; Haq, Afrozul
Highlights: Despite lots of sunshine, vitamin D insufficiency is widespread in India. The breadth of widely used foods, including milk, cheese, margarine, dairy products, and various breakfast drinks, can improve the condition of vitamin D deficiency in Asian countries such as India. For successful and necessary fortification of foods and drinks, with micronutrients successful strategies should be developed and emphasized. There is a need to improve the effectiveness of various fruit drinks and staple foods through fortification of vitamin D, which can reduce vitamin D deficiency in the general population as well as in different age groups. Abstract: India is a densely populated country known for its traditional, cultural and lingual diversity. In India Deficiency of vitamin D is seen in both the genders and among all the age groups. Micronutrient deficiencies are steadily adding to the increasing burden of health related co-morbidities with low dietary calcium and magnesium intake in Indian population. Despite lots of sunshine, vitamin D insufficiency is widespread in India according to the age and regions (50–90%). In order to increase vitamin D intake with normal diet, the food industry will have to find a more effective strategy to improve general health conditions. The breadth of widely used foods, including milk, cheese, margarine, dairy products, and various breakfast drinks, can improve the condition of vitamin D deficiency in Asian countries such as India. The requirements for calculating the necessary micronutrients and vitamin D fortification of foods and drinks, successful strategies should be developed and emphasized. There is need to improve the effectiveness of various fruit drinks through fortification of vitamin D, which can reduce vitamin D deficiency in the general population as well as in different age groups.